2016
DOI: 10.1590/s1677-5538.ibju.2015.0538
|View full text |Cite
|
Sign up to set email alerts
|

Do retractile testes have anatomical anomalies?

Abstract: Objectives:To assess the incidence of anatomical anomalies in patients with retractile testis.Materials and Methods:We studied prospectively 20 patients (28 testes) with truly retractile testis and compared them with 25 human fetuses (50 testes) with testis in scrotal position. We analyzed the relations among the testis, epididymis and patency of the processus vaginalis (PV). To analyze the relations between the testis and epididymis, we used a previous classification according to epididymis attachment to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
4
0
1
Order By: Relevance
“…Therefore, if there is presence of smaller testicular volume then surgical correction is required. However, other studies show that RT is seen as a variant of normal testis as it descends into the scrotum and thus is similar in testicular volume and childbearing capacity as normal testis [4].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, if there is presence of smaller testicular volume then surgical correction is required. However, other studies show that RT is seen as a variant of normal testis as it descends into the scrotum and thus is similar in testicular volume and childbearing capacity as normal testis [4].…”
Section: Discussionmentioning
confidence: 95%
“…One emerging reproductive health problem is Bilateral Retractile Testis (BRT) [4] which is a minor, resolved problem even in childhood in developed countries whereas a major, unresolved issue in our society. Parents either ignore or misunderstand pendulous like testicular retraction which particularly affects sperm motility [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, Kraft et al [ 27 ] have shown that fusion anomalies, although associated with smaller testes, are not associated with significant abnormalities in the germ cell number and testicular histological structure. In turn, Anderson et al [ 28 ] observed a significantly higher prevalence of epididymal anomalies (14%) and patent PV (21%) even in retractile testes. Over 70% of patients with this condition show normal testicular development and function; however, in some cases morphological alterations in the testicular structure were found [ 29 ], as well as poor semen parameters in adulthood [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The measured volume values were compared, and the results showed that the volume in boys with RT was significantly less than the recently determined standard value. Anderson et al ( 69 ) conducted a prospective study of 20 boys with RT (1–12 years old) and 25 human fetuses with the testes in the scrotal position. The age range of the fetuses was 26–35 weeks of gestation.…”
Section: Treatment Of Cryptorchidismmentioning
confidence: 99%